Improving farm efficiency of interacting vertical‐axis wind turbines through wake deflection using pitched struts. Issue 4 (11th January 2019) - Mendoza, Victor; Goude, Anders
Abstract: This work presents a numerical study of the obtained performance and the resulting flow field between two interacting large scale vertical‐axis wind turbines (VAWTs), under the influence of a deflected wake through the struts pitching of the upwind turbine. The configuration consists of two VAWTs aligned in the direction of the incoming flow in which a wide range of fixed struts pitching angles in the upwind turbine have been investigated. The main goal is to evaluate the influence of the wake deflection on the turbines performance while they are operating at their optimal tip speed ratio (TSR), and to reproduce the most relevant phenomena involved in the flow pattern of the interacting wake. Arrangements with cross‐stream offsets have also been tested for quantifying the contribution of this modification into the overall performance. For this purpose, an actuator line model (ALM) has been implemented using the open‐source CFD library OpenFOAM in order to solve the governing equations and to calculate the resulting flow. The Large eddy simulation (LES) approach is considered to reproduce the turbulence flow effects. A preliminary study to identify the optimal TSR of the interacting downwind turbine has been investigated.